Pengaruh Efektivitas implementasi e-Parkir pada Area Pasar Induk Among Tani Batu Menggunakan Pendekatan Metode TAM - Zebua, Peter Affandi; Utomo, Listanto Tri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to examine the influence of the effectiveness of the E-Parking system at Pasar Induk Among Tani Batu. The research intends to determine whether the implementation of the information system is effective in managing parking and addressing congestion issues and whether it is well-received by the surrounding community. The sampling technique used is purposive sampling with a sample size of 43 market visitors. Using a descriptive quantitative analysis method, data were collected through questionnaires with a Likert scale. The results of this study indicate that the perceived usefulness variable (X1) has a significant effect on effectiveness (Y). The perceived ease of use variable (X2) has a partially positive effect on the effectiveness variable (Y). The actual use variable (X3) partially affects the effectiveness variable (Y). The E-Parking system is well-received by users and effective in addressing parking issues at Pasar Induk Among Tani Batu.